2015
DOI: 10.1016/j.tox.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

PINK1/Parkin-mediated mitophagy alleviates chlorpyrifos-induced apoptosis in SH-SY5Y cells

Abstract: Chlorpyrifos (CPF) is one of the most widely used organophosphorous insecticides. There are links between CPF exposure and neurological disorders. Mitochondrial damage has been implicated to play a key role in CPF-induced neurotoxicity. Mitophagy, the selective autophagic elimination of mitochondria, is an important mitochondrial quality control mechanism. However, the role of mitophagy in CPF-induced neurotoxicity remains unclear. In this study, CPF-caused mitochondrial damage, role and mechanism of mitophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Impaired mitochondria were found in CPF‐treated neuronal cells. The CPF exposure induced mitophagy, which was cytoprotective for CPF‐induced apoptosis in SHSY‐5Y cells . The altered mitochondrial dysfunction was associated with ROS generation in both cell lines (cf Figure ).…”
Section: Discussionmentioning
confidence: 88%
“…Impaired mitochondria were found in CPF‐treated neuronal cells. The CPF exposure induced mitophagy, which was cytoprotective for CPF‐induced apoptosis in SHSY‐5Y cells . The altered mitochondrial dysfunction was associated with ROS generation in both cell lines (cf Figure ).…”
Section: Discussionmentioning
confidence: 88%
“…Conversely, CPF decreased cell proliferation in a dose‐dependent manner in both cell lines. Mitochondrial damage has been implicated to play a key role in pesticide‐induced neurotoxicity . We showed that GLY and CPF treatment caused increased mitochondrial activity at low doses, while inhibiting mitochondrial activity at higher concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…However, in both European Society of Urogenital Radiology and the Kidney Disease: Improving Global Outcomes guidelines, either IOCM or LOCM was recommended in patients with increased risk of CI-AKI [28, 29]. Mounting evidence demonstrated that ROS generation and mitochondrial membrane depolarization may lead to DNA damage and apoptosis [30, 31]. Recent studies indicated that an excess generation of mitochondrial ROS played an important role in the pathogenesis of AKI [32, 33].…”
Section: Discussionmentioning
confidence: 99%